Cell-Free DNA Quantification and Methylation Status of DCC Gene as Predictive Diagnostic Biomarkers of Lung Cancer in Patients Reported at Gulab Devi Chest Hospital, Lahore. (December 2017) - Aslam, Muhammad Shahbaz; Shaeer, Abeera; Abbas, Zaigham; Ahmed, Aftab; Gull, Iram; Athar, Muhammad Amin
The worldwide high mortality rate of lung cancer could be reduced significantly by its noninvasive early detection. The quantitative analysis of cell-free circulating DNA in plasma presents a potential noninvasive approach for liquid biopsy of tumor. In this study, real-time polymerase chain reaction–based approach was used to quantify free circulating DNA in plasma. The concentration of free circulating DNA was checked using human telomerase reverse transcriptase gene as marker, and amplification status of oncogene RAC-β serine/threonine protein kinase along with the DNA methylation status of tumor suppressor gene (deleted in colorectal cancer) was assessed. The concentration of free circulating DNA in patients with lung cancer (22.8 ng/mL) was found approximately 6 times above than the value detected in controls (2.8 ng/mL). Considerable variation in the AKT2 copy number was observed in patients with lung cancer and controls ( P < .000). Aberrant methylation of the deleted in colorectal cancer promoter was found to be highly specific (100%), as none of the control plasma samples showed aberrant methylation. The quantification of free circulating DNA along with determination of AKT2 amplification and deleted in colorectal cancer promoter methylation status appeared promising to differentiate patients with lung cancer from healthy individuals.